2020
DOI: 10.12659/msm.920846
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of mRNA expression profiling in Parkinson’s Disease

Abstract: Departmental sources Background: Parkinson's disease (PD) is a degenerative neurologic disease. This study aimed to undertake bioinformatics analysis using the publicly available Gene Expression Omnibus (GEO) database to integrate mRNA expression data from patients with PD and to compare differentially expressed genes (DEGs) in tissue from the substantia nigra and whole blood from patients with PD and normal controls. Material/Methods: Integrated network analysis included GEO datasets to identify DEGs in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…2C). Reduced expression of ALDH1A1 in the substantia nigra of patients with PD 39 is consistent with our results (Fig. 2D).…”
Section: Discussionsupporting
confidence: 93%
“…2C). Reduced expression of ALDH1A1 in the substantia nigra of patients with PD 39 is consistent with our results (Fig. 2D).…”
Section: Discussionsupporting
confidence: 93%
“…Research has identified several genetic or environmental factors that may contribute to the neurodegeneration associated with osteoporotic conditions. First, Wnt/β-catenin signaling has attracted attention because aberrant Wnt/β-catenin signaling has been reported to affect both osteoporosis and neurodegenerative diseases, including Parkinson’s and Alzheimer’s diseases (Li et al, 2013 ; Folke et al, 2019 ; Wang and Wang, 2020 ). Approximate percentages of patients with AD, PD, or osteoporosis who have a pathogenic variant of Wnt/β-catenin signaling have not yet been established.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last two decades, epidemiological studies have highlighted the potential link between osteoporosis and the risk of neurodegenerative disease (Yaffe et al, 1999;Tan et al, 2005;Zhou et al, 2011;Chang et al, 2014;Roos, 2014;Amouzougan et al, 2017;Kostev et al, 2018;Feng et al, 2021). Experimental evidence supports that molecular alterations and chemical exposure mediate the pathogenic changes associated with AD and PD in osteoporotic animal models (Li et al, 2013(Li et al, , 2014Calabrese et al, 2016;Folke et al, 2019;Wang and Wang, 2020;Abdul-Latif et al, 2021;Jiang et al, 2021), and researchers assume they may share some central mechanisms. While the majority of epidemiological studies have focused on the effect of osteoporosis on the risk of AD or dementia (Yaffe et al, 1999;Tan et al, 2005;Zhou et al, 2011;Chang et al, 2014;Roos, 2014;Amouzougan et al, 2017;Kostev et al, 2018), data for the relation to PD risk are scarce (Feng et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, transcriptome analyses of postmortem brain tissue samples obtained by LCM have revealed spatiotemporal changes in the expression levels of various genes associated with PD 36,41 . Furthermore, recent bioinformatics analysis using publicly available Gene Expression Omnibus database, comparing differentially expressed genes in PD patients and normal controls, revealed that sortilin is upregulated in the substantia nigra of PD and serves as a hub molecule in the protein–protein interaction network 42 . Given this situation, we used a publicly available RNA‐seq dataset of neuromelanin‐containing midbrain dopaminergic neurons obtained from the brain samples of PD and ILBD to evaluate the expression profile of sortilin during disease progression (Figure 6C,D).…”
Section: Resultsmentioning
confidence: 99%